Lesinurad: Evaluation of Pharmacokinetic and Pharmacodynamic Interactions With Warfarin in Healthy Volunteers. Issue 5 (13th February 2019) - Shen, Zancong; Lee, Caroline A.; Wallach, Kathleen; Valdez, Shakti; Wilson, David M.; Kerr, Bradley; Gillen, Michael
Abstract: Lesinurad is a selective uric acid reabsorption inhibitor approved for use in combination with xanthine oxidase inhibitors for the treatment of hyperuricemia associated with gout. In vitro, lesinurad was shown to be a weak inhibitor of cytochrome P450 (CYP)2C9 and a weak inducer of CYP3A4. Warfarin is a widely prescribed oral coumarin‐based anticoagulant commonly prescribed in gout patients. In an open‐label clinical study in healthy adult male subjects, the effects of multiple daily doses of 400 mg lesinurad on the pharmacokinetics and pharmacodynamics of a single dose of 25 mg warfarin (racemic mixture of R‐ and S‐ enantiomers) were evaluated. Lesinurad had no effect on the absorption or the exposure (area under the concentration‐time curve [AUC] and peak concentration) of the more active S‐warfarin enantiomer. A slight reduction (19%) in overall plasma exposure (AUC) was observed for the R‐warfarin enantiomer. Lesinurad had no meaningful clinical impact on anticoagulation activity as measured by prothrombin time, activated partial thromboplastin time, and international normalized ratio of prothrombin time and Factor VII clotting activity. Overall, the administration of warfarin in the presence of multiple‐dose lesinurad was devoid of clinically significant drug‐drug interaction.